QUIZZZ MEDIA AS AN ASSESSMENT FOR HISTORY LEARNING IN THE DIGITAL ERA - Pangestu, Rani Samudra; Fahruddin, Fahruddin (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Mataram, 2024)
Current history learning, in general, still uses a conventional approach with students learning in class through lectures, questions and answers, and assignments. Traditional history learning results in students only working procedurally and understanding history without reasoning, which tends towards behavioral and structuralist psychology and places more emphasis on memorization and practice. This approach uses a qualitative approach with descriptive data. In discussing the problem in this article, the author uses a type of library research. Teachers can take advantage of advances in information technology by using learning media. Quizizz is one of the media innovations in history learning assessment activities. Digital media as a learning assessment has experienced significant development. Digital media offers various educational innovations that replace rigid and monotonous conventional learning and assessment, which will be replaced with learning that is considered more practical, flexible, and not limited by space and time using digital media. Quizizz can be a good and fun assessment of history learning while maintaining the essence of ongoing learning. This assessment can involve active student participation from the start. Apart from that, the demands in the era of Industrial Revolution 4.0 have changed various sectors of life, including the education sector, which needs to be reoriented to determine the direction of education policy to answer the challenges of Industrial Revolution 4.0.